2020
DOI: 10.1002/jaba.776
|View full text |Cite
|
Sign up to set email alerts
|

Technology‐based versus in‐person deposit contract treatments for promoting physical activity

Abstract: Deposit contracts involve participants depositing their own money and earning it back contingent on behavior change. Deposit contracts are empirically supported treatments for promoting health behavior, but they have a history of poor uptake. We compared the effectiveness and acceptability of technology-based versus in-person deposit contracts for promoting physical activity with 12 individuals. Participants' daily step counts were monitored using Fitbits across 6 weeks, and treatment preferences were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 42 publications
(61 reference statements)
3
21
0
Order By: Relevance
“…In addition to the special series on public health in this journal, a 2019 special issue of Perspectives on Behavior Science focused on addictions, and showcased substantial basic, translational, applied, and public health contributions of behavior analysis (Washington & Galizio, 2019). Recent conceptual and empirical work has focused on diabetes prevention and management (Raiff et al, 2020), disease transmission in the workplace (Gravina et al, 2020) injury prevention in sports (Quintero et al, 2020;Harris et al, 2020), physical activity (Nieto & Wiskow, 2020;Stedman-Falls & Dallery, 2020), cigarette smoking (Dallery et al, 2021), and health and wellness coaching (Finn & Watson, 2017;Normand & Bober, 2020). The strengths of behavior analysis (e.g., rigorous experimental methods, conceptual account of the causes of health behavior) increase the chances, but do not guarantee, that behavioral technology may lead to public health impact (Hantula, 2019).…”
Section: Do More Of What We Are Doingmentioning
confidence: 99%
“…In addition to the special series on public health in this journal, a 2019 special issue of Perspectives on Behavior Science focused on addictions, and showcased substantial basic, translational, applied, and public health contributions of behavior analysis (Washington & Galizio, 2019). Recent conceptual and empirical work has focused on diabetes prevention and management (Raiff et al, 2020), disease transmission in the workplace (Gravina et al, 2020) injury prevention in sports (Quintero et al, 2020;Harris et al, 2020), physical activity (Nieto & Wiskow, 2020;Stedman-Falls & Dallery, 2020), cigarette smoking (Dallery et al, 2021), and health and wellness coaching (Finn & Watson, 2017;Normand & Bober, 2020). The strengths of behavior analysis (e.g., rigorous experimental methods, conceptual account of the causes of health behavior) increase the chances, but do not guarantee, that behavioral technology may lead to public health impact (Hantula, 2019).…”
Section: Do More Of What We Are Doingmentioning
confidence: 99%
“…The extent to which our findings generalize to persons less interested in exercising, with different health statuses, or time commitments is unknown. In addition, the magnitude of the self-tailored deposit contracts in our study (between $300 and $600) was substantially greater than the amount used in prior work (Donlin Washington et al, 2016;Jarvis & Dallery, 2017;Kerrigan et al, 2020;Stedman-Falls & Dallery, 2020). Not everyone has the means or is willing to wager such amounts of money.…”
Section: Discussionmentioning
confidence: 60%
“…Third, communication and delivery of reinforcement was online. This is important because it further strengthens support for technology-based interventions that remove physical barriers that might otherwise preclude someone from participating (see Kerrigan et al, 2020;Stedman-Falls & Dallery, 2020). In addition, advances in technology and systems such as FitLinxx allow data to be readily and objectively detected without the presence of researchers or clinicians.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In 2012, Van Camp and Hayes reviewed the effects of behavioral interventions on physical activity and reported that although there is some evidence to suggest positive outcomes of behavioral interventions (e.g., self-monitoring and contingency management) at increasing activity, these authors also identified the need for additional research. Several more recent studies have demonstrated that behavioral interventions such as contingent incentives and deposit contracts can improve a number of behaviors related to physical activity, including daily steps taken (Finkelstein et al, 2013; Kurti & Dallery, 2013; Stedman-Falls & Dallery, 2020; Washington et al, 2014, 2016) and gym attendance (Beatty & Katare, 2018; Carrera et al, 2018; see Barte & Wendel-Vos, 2017, for a systematic review). For example, Pope and Harvey (2014) used a group design to analyze the effects of contingent weekly monetary rewards on college students’ participation in 30-min physical activity sessions.…”
mentioning
confidence: 99%